Diversity and community composition of fishes in the Pusu River Gombak, Malaysia - Khan Chowdhury, Ahmed Jalal; Alifah, F.K.; Nordin, Noor Faizul Hadry; Al-Mamun, Abdullah; Kader, M.A.; Ashraf, Muhammad Aqeel (Coastal Education & Research Foundation Inc. Florida, 2018)
The Pusu River has been receiving increased pollution loads because of a significant amount of land-clearing activities for development projects. A total of 113 numbers of fishes belonging to six species under six families were recorded from Pusu River throughout the study period (November 2014–March 2015). The most dominant species were Barbonymus schwanenfeldii (38.9%) followed by Oreochromis mossambica (36.28%) under families Cyprinidae and Cichlidae, respectively. Similarly, the species Hypostomus plecostomus (10.62%), Channa striatus (6.19%), Notopterus notopterus (4.42%), Pristolepis fasciata (3.54%) under the family Loricariidae, Channidae, Notopteridae, and Pristolepididae were constituted of the total fish catch, respectively. A greater abundance (56.64%) of fish community was observed at station 3 compared to the other stations. This is a deeper pool area located near the rainforest area with less turbid water compared to the other stations. Second highest abundance (14.16%) was observed at station 2, while station 6 has shown the lowest abundance (2.65%). Overall Shannon diversity value (H0 ¼ 1.399) indicates that Sg. Pusu, Gombak, is not highly diverse with the tropical fish species. The study suggests that a long-term continuous monitoring of water quality and fish diversity is needed to study for sustainable development of fishes in this fascinating tropical river (Sg.) Pusu.